2011
DOI: 10.1039/c1dt10461f
|View full text |Cite
|
Sign up to set email alerts
|

Copper(i) 2-pyridyl selenolates and tellurolates: Synthesis, structures and their utility as molecular precursors for the preparation of copper chalcogenide nanocrystals and thin films

Abstract: The complexes, [Cu{EC(5)H(3)(R-3)N}](4) (E/R = Se/Me or Te/R; R = H or Me) were isolated by the reaction between CuCl and NaEC(5)H(3)(R-3)N and were characterized by elemental analyses, uv-vis and NMR ((1)H, (13)C) spectroscopy. The crystal structures of [Cu{SeC(5)H(3)(Me-3)N}](4) and [Cu(TeC(5)H(4)N)](4) revealed that the molecules are tetrameric in which each copper atom lies at the vertex of the tetrahedron and each face of the tetrahedron is capped by the bridging pyridylchalcogenolate ligand. Thermal beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 61 publications
(28 citation statements)
references
References 48 publications
1
27
0
Order By: Relevance
“…The crystal structure of [Cu(TeC 5 H 4 N)] 4 revealed that the molecules are tetrameric — each copper atom lies at the vertex of the tetrahedron and each face of the tetrahedron is capped by the bridging pyridylchalcogenolate ligand. This suggests that 8 is the possible intermediate of [Cu(TeC 5 H 4 N)] 4 …”
Section: Resultsmentioning
confidence: 99%
“…The crystal structure of [Cu(TeC 5 H 4 N)] 4 revealed that the molecules are tetrameric — each copper atom lies at the vertex of the tetrahedron and each face of the tetrahedron is capped by the bridging pyridylchalcogenolate ligand. This suggests that 8 is the possible intermediate of [Cu(TeC 5 H 4 N)] 4 …”
Section: Resultsmentioning
confidence: 99%
“…Metal complexes based on ligands containing chalcogen atom and nitrogen donor, in particular, have not only been used as catalysts in C-C coupling reactions, 7-10 but have also emerged as versatile molecular precursors for metal chalcogenide nanomaterials. [11][12][13] Recently we have examined the chemistry of palladium and platinum complexes derived from two different classes of hemilabile ligands, viz. N,N-dimethylaminoalkylchalcogenolate [14][15][16][17][18][19] and 2-pyridylchalcogenolate.…”
Section: Introductionmentioning
confidence: 99%
“…6 N-heterocyclic thiolate complexes of coinage metals are fairly well investigated; 6,7 however, the heavier chalcogenolate (Se or Te) complexes have received attention only recently. 8 The hexanuclear ijAg{SeC 4 HIJMe-4,6) 2 N 2 }] 6 has been successfully employed as a molecular precursor for the synthesis of monodispersed Ag 2 Se nanoparticles. 8 Of late solution phase pyrolytic methods have emerged as a successful strategy to prepare metal chalcogenide nanomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…8 The hexanuclear ijAg{SeC 4 HIJMe-4,6) 2 N 2 }] 6 has been successfully employed as a molecular precursor for the synthesis of monodispersed Ag 2 Se nanoparticles. 8 Of late solution phase pyrolytic methods have emerged as a successful strategy to prepare metal chalcogenide nanomaterials. 8,9 The homoleptic silver chalcogenolate complexes are polymeric and are insoluble in common organic solvents, thus limiting their utility as precursors for the preparation of silver-chalcogenides.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation